Investigation of Virulence Genes by PCR in Stapylococcus aureus Isolates Originated from Subclinical Bovine Mastitis in Turkey - Karahan, Murat; Acik, Mehmet Nuri; Cetinkaya, Burhan (Univ Agriculture, Fac Veterinary Science, 2011)
The aim of the present study was to characterize coagulase (coa) positive Staphylococcus aureus strains (n=92) isolated from bovine subclinical mastitis in Turkey by PCR amplification of clumping factor A (clfA) and protein A (spa) genes. All the coa-positive S. aureus isolates were determined to harbor the genes encoding the IgG binding region (spa-IgG) and the X region (spa-X) of spa. On the other hand, 84 (91.3%) isolates were positive for clfA gene. These three genes displayed size polymorphisms. It was concluded that spa gene polymorphisms for S. aureus, when used together with coa-PCR, can be proposed as good alternatives to conventional methods in typing S. aureus isolates of bovine origin which may provide valuable data for the development of effective control strategies against staphylococcal mastitis. The results of the present study showed that S. aureus isolates responsible for the mastitis cases in Turkey were genetically diverse. (C) 2011 PVJ. All rights reserved
Keywords: Mastitis; PCR; Staphylococcus aureus; Virulence Genes